The Impact of Investment and Labor on Gross Regional Domestic Product (GRDP) in West Aceh Regency during the 2014–2025 Period - Rahmah Tulfitri; Affandi Affandi; Okta Rabiana Risma (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Gross Regional Domestic Product (GRDP) is one of the primary indicators used to measure the economic performance and growth of a region. GRDP growth is influenced by various production factors, particularly investment and labor. This study aims to examine the effects of investment and labor on the Gross Regional Domestic Product (GRDP) of West Aceh Regency during the 2014–2025 period, both partially and simultaneously. A quantitative approach was employed using secondary data obtained from official publications of relevant government institutions. The data were analyzed using multiple linear regression, preceded by classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. Hypotheses were subsequently tested using the partial t-test, simultaneous F-test, and the coefficient of determination (R²). The findings indicate that investment has a positive and statistically significant effect on the GRDP of West Aceh Regency at the 90% confidence level. Labor also has a positive and significant effect on GRDP, indicating that increased labor absorption enhances production capacity and regional economic activities. Furthermore, investment and labor jointly have a significant influence on GRDP. The coefficient of determination (R²) of 0.532 indicates that 53.2% of the variation in GRDP can be explained by these two variables, while the remaining 46.8% is influenced by other factors not included in the research model. Originality: These findings confirm that increasing investment, supported by productive labor absorption, is a key driver of regional economic growth. Therefore, local governments should strengthen policies that encourage investment, improve the quality of human resources, and expand employment opportunities to promote sustainable economic growth.